MAXIMAL TEMPORAL AMPLITUDE (MTA) OF TRI-CHROMATIC SIGNALS - Marwan . (Proceedings of ICMSA, 2005)
Previous numerical and experimental results about surface waves whichare originally bi-chromatic signal on the wave maker, showphenomenon about peaking and splitting dwing their propagation in thewave tank. To investigate this phenomenon, especially in peaking, aquantity called Maximal Temporal Amplitude (MTA) is introduced.This quantity can be used to predict the position of the occurrence ofmaximal peaking. ln this paper, we present the MTA form of tricluomaticsignal, especially to predict the position of maximal peakingof the signal. Here, the tri-chromatic signal is a superposition of threemono-chromatic signals with different of amplitudes, frequencies andinitial phases. We use KdV equation with exact dispersion relation(linear) as a model. We get some approximated solution by expandingthe equation in the power series of amplitude and wave number of trichromaticsignal up to third order.Keywords : Phase tri-chromatic signal, Maximal Temporal Amplitude